Differential arthritogenicity of Staphylococcus aureus strains isolated from biological samples - Colavite-Machado, Priscila M. [UNESP]; Ishikawa, Larissa Lumi W. [UNESP]; Donegá França, Thaís G. [UNESP]; Zorzella-Pezavento, Sofia Fernanda G. [UNESP]; da Rosa, Larissa C. [UNESP]; Chiuso-Minicucci, Fernanda [UNESP]; da Cunha, Maria de Lourdes Ribeiro de Souza [UNESP]; Garlet, Gustavo P.; Sartori, Alexandrina [UNESP] (Springer Nature, 2013)
Background: Staphylococcus aureus is the most common agent of septic arthritis that is a severe, rapidly progressive and destructive joint disease. Superantigens produced by S. aureus are considered the major arthritogenic factors. In this study, we compared the arthritogenic potential of five superantigen-producing staphylococcal strains.Methods: Male C57BL/6 mice were intravenously infected with ATCC 19095 SEC+, N315 ST5 TSST-1+, S-70 TSST-1+, ATCC 51650 TSST-1+ and ATCC 13565 SEA+ strains. Clinical parameters as body weight, arthritis incidence and clinical score were daily evaluated. Joint histopathological analysis and spleen cytokine production were evaluated at the 14th day after infection.Results: Weight loss was observed in all infected mice. ATCC 19095 SEC+, N315 ST5 TSST-1+ and S-70 TSST-1+ were arthritogenic, being the highest scores observed in ATCC 19095 SEC+ infected mice. Intermediate and lower clinical scores were observed in N315 ST5 TSST-1+ and S-70 TSST-1+ infected mice, respectively. The ATCC 13565 SEA+ strain caused death of 85% of the animals after 48 h. Arthritis triggered by the ATCC 19095 SEC+ strain was characterized by accentuated synovial hyperplasia, inflammation, pannus formation, cartilage destruction and bone erosion. Similar joint alterations were found in N315 ST5 TSST-1+ infected mice, however they were strikingly more discrete. Only minor synovial proliferation and inflammation were triggered by the S-70 TSST-1+ strain. The lowest levels of TNF-α, IL-6 and IL-17 production in response to S. aureus stimulation were found in cultures from mice infected with the less arthritogenic strains (S-70 TSST-1+ and ATCC 51650 TSST-1+). The highest production of IL-17 was detected in mice infected with the most arthritogenic strains (ATCC 19095 SEC+ and N315 ST5 TSST-1+).Conclusions: Together these results demonstrated that S. aureus strains, isolated from biological samples, were able to induce a typical septic arthritis in mice. These results also suggest that the variable arthritogenicity of these strains was, at least in part, related to their differential ability to induce IL-17 production. © 2013 Colavite-Machado et al.; licensee BioMed Central Ltd.
Keywords: IL-17; Septic arthritis; Staphylococcus aureus